Baloy Kabalat a community and cultural center for the Dumagats of San Jose del Monte, Bulacan - Ahiyal, Mhariam A.; Lico, Gerard Rey A. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
"Baloy Kabalat", derived from the Dumagat Bulos words "Baloy" and "Kabalat" which means "home" and "member of the community", respectively, is a home for the Dumagat community. It is a community and cultural center for the Dumagat of San Jose del Monte City of Bulacan that glorifies the history and culture of the Dumagat group that once prevailed in the land of San Jose del Monte. In search of the city's identity and the rapid urbanization that it faces, the project gives way in finding the core of the city's identity while targeting the development of the marginalized people who were usually being left out and disenfranchised as the city urbanizes. Tailored with the Dumagats' culture and needs, the program of the project gives a space for the Dumagat to preserve their culture through continuing its development by living through it, showing how the Dumagat culture has evolved over the years, to look back on its rich past, and to preserve the old way of Dumagat living. Withwhich, it consists of cultural center spaces and visitor center and basic community center spaces such as school, livelihood center and health center. With the continuous flow of time and the inevitable changes, still, some practices remain constant. Truly, no matter how the Dumagats evolve through time, they would always anchor themselves to the simplicity of life that the mountains has offered them. Nonetheless, the main purpose of this project is to create a sustainable development that will revitalize the culture of the city and at the same time, will encourage an inclusive development for the city of San Jose del Monte, Bulacan.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Cities and towns -- Growth; Indigenous peoples -- Urban residence -- Philippines